PINCH proteins regulate cardiac contractility by modulating integrin-linked kinase-protein kinase B signaling - Meder, Benjamin; Huttner, Inken G.; Sedaghat-Hamedani, Farbod; Just, Steffen; Dahme, Tillman; Frese, Karen S.; Heilmeier, Britta; Köhler, Doreen; Kloos, Wanda; Rudloff, Jessica; Marquart, Sabine; Katus, Hugo; et al. (Molecular and cellular biology, 2011)
Integrin-linked kinase (ILK) is an essential component of the cardiac mechanical stretch sensor and is bound in a protein complex with parvin and PINCH proteins, the so-called ILK-PINCH-parvin (IPP) complex. We have recently shown that inactivation of ILK or β-parvin activity leads to heart failure in zebrafish via reduced protein kinase B (PKB/Akt) activation. Here, we show that PINCH proteins localize at sarcomeric Z disks and costameres in the zebrafish heart and skeletal muscle. To investigate the in vivo role of PINCH proteins for IPP complex stability and PKB signaling within the vertebrate heart, we inactivated PINCH1 and PINCH2 in zebrafish. Inactivation of either PINCH isoform independently leads to instability of ILK, loss of stretch-responsive anf and vegf expression, and progressive heart failure. The predominant cause of heart failure in PINCH morphants seems to be loss of PKB activity, since PKB phosphorylation at serine 473 is significantly reduced in PINCH-deficient hearts and overexpression of constitutively active PKB reconstitutes cardiac function in PINCH morphants. These findings highlight the essential function of PINCH proteins in controlling cardiac contractility by granting IPP/PKB-mediated signaling.